Morphology‐Controlled Self‐Assembly and Nanostructured NiO: An Eﬃcient and Robust Photocatalytic Water‐Oxidation Catalyst. Issue 15 (26th June 2015) - Du, Xiaoqiang; Ding, Yong; Li, Chengqiang
Abstract Three α‐NiO nanocompounds of different morphology, with nanorods, nanowires, and nanoplates, were synthesized by controlling the ratio of reactants and temperature. The shape and structure of the nanocompounds were confirmed by SEM, XRD, FTIR, Raman spectroscopy, energy‐dispersive X‐ray spectroscopy, BET, and X‐ray photoelectron spectroscopy (XPS) analysis. These compounds were examined as catalysts in photocatalytic water oxidation with [Ru(2, 2′‐bipyridine)3]2+ and S2O82− as a photosensitizer and a sacrificial oxidant, respectively. All of the samples exhibit high turnover frequencies and perfect stability in slightly alkaline conditions. A characteristic peak at around E=0.95 V versus Ag/AgCl assigned to a Ni3+ species was detected by cyclic voltammetry, which suggests that a high‐valent nickel species may be responsible for water oxidation. The surface properties of the α‐NiO nanorods also remain unchanged after examination by XPS before and after the photocatalytic reaction.